Single dose 17 alpha-hydroxyprogesterone caproate in preterm labor: a randomized trial. - Tan, P.C.; King, A.S.J.; Vallikkannu, N.; Omar, S.Z. (Springer Verlag (Germany), 2011)
OBJECTIVE: To evaluate the effect of a single 250-mg dose of 17 alpha-hydroxyprogesterone caproate (17-OHPC) intramuscularly as adjunct to nifedipine tocolysis in preterm labor.